Ki-67 pulmonary immunoreactivity in silver nanoparticles toxicity: Size-rate dependent genotoxic impact. (2022) - Ali, Sanaa A.; Kadry, Mai O.; Hammam, Olfat; Hassan, Sohair A.; Abdel-Megeed, Rehab M.
Abstract: Engineered nanoparticles have been recently utilized in numerous domains particularly, silver nanoparticles (AgNPs). Nonetheless, the possible side effects resulting from AgNPs exposure are not fully clarified. The present study was designed to clarify the toxicity of AgNPs on lung tissue. Furthermore, therapeutic impact of Glycosmis pentaphylla (G. pentaphylla) and Casimiroa edulis (C. edulis) leaves extracts in addition to mucilage and protein (the purified compounds from C. edulis ) was investigated against AgNPs induced pulmonary toxicity. Male Swiss albino mice were administered AgNPs orally in two different particle sizes (20 nm and 100 nm) for one month and was further treated via G. pentaphylla, C. edulis, mucilage and protein in a dose of 500 mg/ kg for three weeks. Biochemical, molecular, immunohistochemistry, and histopathological investigations were further assessed. An obvious alteration in oxidative stress biomarkers as well as mRNA gene expression of both survivin and matrix metalloproteinase (MMP-9) was recorded in AgNPs intoxicated group. In addition to, exploration of positive nuclei for Ki-67 was also observed upon AgNPs intoxication. Data declared a significant improvement in the assessed parameters upon G. pentaphylla, C. edulis, mucilage and protein treatment. In conclusion; G. pentaphylla and C. edulis extracts could be considered as a promising candidate as therapeutic regimen against pulmonary toxicity induced via AgNPs due to their enrichment with different active constituents. Practical applications: Due to the expansion of AgNPs applications, it is urgent to investigate their toxic impact associated with release of free silver ions. Different particle sizes of AgNPs can induce various alterations in cellular biochemical parameters, mRNA gene expression, histopathological and immunohistopathological examination. Herein, this natural products extracts are used for the first time as promising therapeutic regimen to ameliorate the toxic effect in AgNPs intoxicated lung tissue in mice model as a result of the bioactive metabolites, especially flavonoids and polyphenolic compounds. Graphical Abstract: ga1 Highlights: Silver nanoparticles (AgNPs) are commonly utilized in several consumer products. The present study was designed to clarify the toxic effect of AgNPs on lung tissue. The therapeutic impact of Glycosmis pentaphylla and Casimiroa edulis extracts against AgNPs induced pulmonary toxicity. .Biochemical, molecular, immunohistochemistry, and histopathological investigations were further assessed. AgNPs illustrated an obvious alteration in oxidative stress biomarkers, survivin, MMP-9 and positive nuclei for ki-67. Upon natural Products treatment, the assessed parameters were modulated. The G. pentaphylla and C. edulis could be promising candidates against AgNPs lung toxicity.